Sex-Specific Differences of Adenosine Triphosphate Levels in Red Blood Cells Isolated From ApoE/LDLR Double-Deficient Mice - Alcicek, Fatih Celal; Mohaissen, Tasnim; Bulat, Katarzyna; Dybas, Jakub; Szczesny-Malysiak, Ewa; Kaczmarska, Magdalena; Franczyk-Zarow, Magdalena; Kostogrys, Renata; Marzec, Katarzyna M. (Frontiers in Physiology, 2022)
In this study for the first time, we investigated the correlation between sex-specific differences in ATP levels in red blood cells (RBCs) and their mechanical, biochemical, and morphological alterations during the progression of atherosclerosis in ApoE/LDLR double-deficient (ApoE/LDLR-/-) mice. Our results indicate that both sex and age affect alterations in RBCs of both ApoE/LDLR-/- and C57BL/6J mice. When compared with male RBCs, female RBCs were characterised by lower basal ATP and MCHC, higher HGB, MCV, MCH, deformability and PS exposure levels, regardless of age in both, ApoE/LDLR-/- and C57BL/6J mice. ApoE/LDLR-/- mice compared with age-matched controls showed lower basal ATP levels regardless of age and sex. Intracellular ATP level of RBCs was decreased solely in senescent female C57BL/6J mice, while it was elevated in males. Basal extracellular ATP levels were 400 times lower than corresponding intracellular level. In conclusion, basal ATP levels, RBC morphology, deformability, PS exposure levels alterations are sex-dependent in mice. Changes in basal ATP levels were correlated with PS exposure and trends of changes in MCV. Trends of changes of the most RBC parameters were similar in both sexes of ApoE/LDLR-/- mice compared with age-matched controls, however, their kinetics and levels vary greatly between different stages of disease progression.